Protective effect of vitamin D on Luteinizing Hormone (LH), Follicle-Stimulating Hormone (FSH), testosterone hormones and testicular tissue changes induced by methotrexate in adult male rats - Mahnaz Dehghani; Mehrdad Shariati; Davood Moghadamnia (مجله دانشگاه علوم پزشکی بیرجند, 2022)
Background and Aims: Vitamin D has antioxidant and anti-inflammatory activities. The present study aimed to investigate the protective effect of vitamin D on Luteinizing Hormone (LH), Follicle-Stimulating Hormone (FSH), testosterone hormones and testicular tissue changes induced by methotrexate in adult male rats. Materials and Methods: In this experimental study, 30 adult male Wistar rats weighing 230-260 g were divided into six groups (n=5). Control group: They received no extract or solvent, sham group: 1 ml of distilled water as a solvent, treatment group 1: methotrexate (5 mg/kg) (gavage), treatment group 2: vitamin D (1000 IU/kg), treatment group 3: methotrexate (5 mg/kg) + vitamin D (500 IU/kg), and treatment group 4: methotrexate (5 mg/kg) + vitamin D (1000 IU/kg). After 28 days of treatment in the form of gavage, blood was taken directly from the heart to measure the serum concentration of LH, FSH, and testosterone hormones. The testes were removed and tissue changes were examined with hematoxylin-eosin staining. The collected data were analyzed using SPSS (version 18), one-way analysis of variance, and post hoc Tukey's test. Results: In the group receiving methotrexate, the level of testosterone hormone, the number of spermatogonia (P>0.001), spermatocytes (P>0.001), sperm (P>0.001) and Leydig cells (P>0.001) decreased and the serum level of LH (P>0.001) and FSH (P>0.001) increased significantly compared to the control and sham groups. In groups receiving methotrexate + vitamin D, vitamin D was able to compensate for the adverse effects caused by methotrexate. Conclusion: Our results showed that vitamin D could improve LH, FSH, testosterone hormones, and testicular tissue changes induced by methotrexate in adult male rats.